Membrane-based conceptual design of reuse water production from candy factory wastewater - Hanna Kyllönen (IWA Publishing, 2021)
Intense pressure on water resources has led to efforts to reuse reclaimed processing wastewater in the food industry. There are tight rules for water quality, but efficient separation technologies such as reverse osmosis possess good possibilities for water reuse. This study developed a membrane-based reuse water concept for wastewater from the candy industry emphasizing the pre-treatment stage in the concept to reduce fouling. The wastewater contained suspended solids, sugar compounds and the ingredients for candy gelation, which had a tendency to foul membranes, making pre-treatment essential for a successful concept. Cross-rotational ultrafiltration, which featured enhanced fouling prevention for membranes, functioned well for the removal of challenging substances. Conventional filtration technologies were impractical due to a low flux, even when the viscosity of the wastewater was reduced using surfactants. The wastewater had a high chemical oxygen demand, meaning that there was a strong fouling potential for reverse osmosis membranes, but also high osmotic pressure. A spiral wound reverse osmosis functioned well when the wastewater was pre-treated, and it produced good quality water with respect to all the other studied parameters except the chemical oxygen demand. However, chemical oxygen demand rejection was 99% since the concentration in the wastewater was originally very high. HIGHLIGHTS A membrane-based concept was successfully applied for water reuse from wastewater.; Cross-rotational ultrafiltration technology enabled chemical-free pre-treatment for wastewater.; Spiral wound reverse osmosis achieved good filtration performance with developed pre-treatment.; Techno-economic evaluation is available for the functional concept.;